Transcription factors define the neuroanatomical organization of the medullary reticular formation - Gray, Paul A. (Frontiers in Neuroanatomy, 2013)
The medullary reticular formation contains large populations of inadequately described, excitatory interneurons that have been implicated in multiple homeostatic behaviors including breathing, viserosensory processing, vascular tone, and pain. Many hindbrain nuclei show a highly stereotyped pattern of localization across vertebrates suggesting a strong underlying genetic organization. Whether this is true for neurons within the reticular regions of hindbrain is unknown. Hindbrain neurons are derived from distinct developmental progenitor domains each of which expresses distinct patterns of transcription factors (TFs). These neuronal populations have distinct characteristics such as transmitter identity, migration, and connectivity suggesting developmentally expressed TFs might identify unique subpopulations of neurons within the reticular formation. A fate mapping strategy using perinatal expression of reporter genes within Atoh1, Dbx1, Lmx1b, and Ptf1a transgenic mice coupled with immunohistochemistry and in situ hybridization were used to address the developmental organization of a large subset of reticular formation glutamatergic neurons. All hindbrain lineages have relatively large populations that extend the entire length of the hindbrain. Importantly, the location of neurons within each lineage was highly constrained. Lmx1b- and Dbx1- derived populations were both present in partially overlapping stripes within the reticular formation extending from dorsal to ventral brain. Within each lineage, distinct patterns of gene expression and organization were localized to specific hindbrain regions. Rostro-caudally sub-populations differ sequentially corresponding to proposed pseudo-rhombomereic boundaries. Dorsal-ventrally, sub-populations correspond to specific migratory positions. Together these data suggests the reticular formation is organized by a highly stereotyped developmental logic.